Mesoporous Fluorocarbon‐Modified Silica Aerogel Membranes Enabling Long‐Term Continuous CO2 Capture with Large Absorption Flux Enhancements. Issue 3 (18th February 2013) - Lin, Yi‐Feng; Chen, Chien‐Hua; Tung, Kuo‐Lun; Wei, Te‐Yu; Lu, Shih‐Yuan; Chang, Kai‐Shiun
Abstract The use of a membrane contactor combined with a hydrophobic porous membrane and an amine absorbent has attracted considerable attention for the capture of CO2 because of its extensive use, low operational costs, and low energy consumption. The hydrophobic porous membrane interface prevents the passage of the amine absorbent but allows the penetration of CO2 molecules that are captured by the amine absorbent. Herein, highly porous SiO2 aerogels modified with hydrophobic fluorocarbon functional groups (CF3) were successfully coated onto a macroporous Al2O3 membrane; their performance in a membrane contactor for CO2 absorption is discussed. The SiO2 aerogel membrane modified with CF3 functional groups exhibits the highest CO2 absorption flux and can be continuously operated for CO2 absorption for extended periods of time. This study suggests that a SiO2 aerogel membrane modified with CF3 functional groups could potentially be used in a membrane contactor for CO2 absorption. Also, the resulting hydrophobic SiO2 aerogel membrane contactor is a promising technology for large‐scale CO2 absorption during the post‐combustion process in power plants.